(untitled) (Research, Society and Development, 2022)
Cancer is a chronic-degenerative disease, usually associated with a history of physical and mental suffering. Currently, advances in cancer treatment are vast, despite them, several studies indicate that there are significant changes in the quality of life of individuals with this diagnosis. The objective of this study was to identify the impacts on the quality of life of patients undergoing cancer treatment. This is a methodological study of an integrative literature review on the specialized cut published between the years 2017 to 2022, which consists of presenting the impact of cancer treatment on people’s quality of life. This research started from an online consultation in the Medline database and in the SciELO library, based on four descriptors in Health Sciences, DeCS – “Oncology”, “Quality of life” and “Chemotherapy”. Thirty-two articles were selected that met the pre-defined criteria for inclusion and exclusion of selected articles. After selection, 5 articles remained within the adopted criteria. The main findings in the searches that refer to an improvement in the quality of life of cancer patients in the included studies were: The impact of diagnosis and treatment is intense and, in most cases, reflects on the physical and mental state of the patient. Which suggests changes in style and quality of life. The study made it possible to identify the main impacts of chemotherapy treatment on patients’ quality of life. Hair loss, loss of smell, loss of appetite, muscle pain, nausea, malaise, vomiting, weight loss or gain, fear, insecurity, depressive symptoms, among others, can be highlighted. Thus, it is necessary for nursing professionals to adopt specific behaviors to alleviate these aspects that compromise the physical and mental health of the affected person.